2015
DOI: 10.1097/prs.0000000000001187
|View full text |Cite
|
Sign up to set email alerts
|

Fat Grafting in Primary Cleft Lip Repair

Abstract: Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 1 publication
0
46
0
Order By: Relevance
“…The efficacy of lipofilling to improve scar appearance has been investigated in 16 case reports or clinical trials (Balkin et al , ; Bollero et al , ; Bruno et al , ; Coleman, ; Guisantes et al , ; Klinger et al , ; Maione et al , ; Mazzola et al , ; Pallua et al , ; Phulpin et al , ; Ribuffo et al , ; Sardesai and Moore, ; Wang et al , ; Zellner et al , ; Table ). In 10 studies of these publications, comprising of a total of 156 patients, complications were recorded: in nine of these 10 studies no complications were recorded, whereas in one study with 12 patients there was a case of cellulitis reported as a complication.…”
Section: Lipofilling As a Methods To Treat Scarsmentioning
confidence: 99%
See 2 more Smart Citations
“…The efficacy of lipofilling to improve scar appearance has been investigated in 16 case reports or clinical trials (Balkin et al , ; Bollero et al , ; Bruno et al , ; Coleman, ; Guisantes et al , ; Klinger et al , ; Maione et al , ; Mazzola et al , ; Pallua et al , ; Phulpin et al , ; Ribuffo et al , ; Sardesai and Moore, ; Wang et al , ; Zellner et al , ; Table ). In 10 studies of these publications, comprising of a total of 156 patients, complications were recorded: in nine of these 10 studies no complications were recorded, whereas in one study with 12 patients there was a case of cellulitis reported as a complication.…”
Section: Lipofilling As a Methods To Treat Scarsmentioning
confidence: 99%
“…Only five well‐designed controlled studies had well‐defined objectives and outcome parameters, and had included both non‐treated (Balkin et al , ; Ribuffo et al , ; Zellner et al , ) or placebo (Bruno et al , ; Maione et al , ) controls. Four of these studies focused on clinical outcomes (Balkin et al , ; Maione et al , ; Ribuffo et al , ; Zellner et al , ) and are discussed below, and one addresses histological changes (Bruno et al , ) and is discussed in the next section.…”
Section: Lipofilling As a Methods To Treat Scarsmentioning
confidence: 99%
See 1 more Smart Citation
“…117 Fat grafts have been shown to improve the appearance of existing scars in five well-designed controlled studies. [118][119][120][121][122] The mechanism of improvement is often reported to be due to the presence of ASCs, however there is a lack of evidence to draw definitive conclusions. 123 More clinical studies are required before cellbased therapy is used clinically.…”
Section: Cell-based Therapymentioning
confidence: 99%
“…In contrast, the use of simple WAT for clinical purposes is not subject to such strict legal restrictions in most countries, as long as it is used as an unpurified autologous lipo-transfer. Current clinical applications include scar treatment, breast reconstruction after breast cancer surgery, aesthetic rejuvenation, cleft-lip repair and liposculpture for body deformities [30,[33][34][35][36]. The treatment of bone defects, osteomyelitis or chronic wounds is being debated [13,30,[35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%